THE PREVALENCE OF OBESITY IN STUDENTS THAT ATTEND TO PHYSICAL EDUCATION CLASSES AT A SCHOOL IN THE CITY OF ITAUEIRA-PI. (Fiep Bulletin - online, 2016)
Obesity and overweight come significantly increasing worldwide in recent years. With technological advances in recent decades, the school became less physically active, which contributed to the increase in overweight and obesity in these groups. It was held a direct descriptive field research with a quantitative approach in order to collect data to determine the prevalence of obesity in schoolchildren that attend to physical education classes of high school at the Municipal School Manoel Bastos Ribeiro in the city of Itaueira-Piaui . The sample by convenience comprised 64 students above 18 years old from the 3rd year of high school. Obesity and overweight were evaluated by body mass index (BMI) and classification was performed according to WHO table having BMI the following parameters:
Keywords: Prevalence; Obesity; School.